Multisystem Langerhans cell histiocystosis in a geriatric patient: case report - Contreras, Diego M.; Gutiérrez, Grecia J. G.; Torres, José M. Z.; Gutiérrez, Félix O. (International Journal of Research in Dermatology, 2022)
Langerhans cell histiocytosis is a condition of exceptional onset characterized by a proliferative event of dendritic cells with mono or multisystem involvement that predominates in the pediatric population and is identified in a smaller proportion in adults. It has a clinical impact and variable prognosis according to its location and number of organs affected. A 68-year-old male patient with clinical and immunohistochemical criteria for Langerhans cell histiocytosis with multisystem settlement with fatal outcome. It is a very rare disease, it is not exclusive to the pediatric population, with little understood pathogenesis and does not have specific treatment. In adults, the clinical impact is more aggressive, with a poorer prognosis and greater short-term complications.